I Cry Out Loud so That God May Hear Me An Intersubjective Use of the Psalms - Gioielli, Chris D. (2021)
This paper explores a theological and intersubjective understanding of praying the psalms in the life of Judeo-Christian faith in order to deepen the way Judeo-Christians and Judeo-Christian leaders pray the psalms. Walter Brueggemann has described praying the psalms as a way to help the Judeo-Christian get more in touch with their faith experiences and with God. The intersubjective psychoanalytic understanding by Jessica Benjamin provides a depth to praying the psalms not only by utilizing Brueggemann's categories, but also enriching them by offering an explanation of the relational processes at play. Intersubjective processes such as mutual recognition and the analytic third provide a deeper understanding for praying the psalms in order to strengthen spiritual and relational intimacy with God.